Development and forecast of 10/40/100 Gbit/s PON technology - Chengliang ZHANG; Qing WANG; Jingwen YU; Fen WAN (Dianxin kexue)
Currently,the evolution of EPON/GPON to higher bitrate technology has become a hot topic in optical access field.Based on this,the current situation and problems of XG(S)-PON,TWDM PON,WDM PON and 100 Gbit/s EPON were analyzed,then some forecast of above technologies was given.